DEVELOPING CHARACTER EDUCATION THROUGH THE SIMPLE SONG COMPOSITION IN ARTS EDUCATION CULTURE FOR JUNIOR HIGH SCHOOL STUDENTS (SMP) - Yos Sudarman; Erfan Lubis (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2015)
MENGEMBANGKAN PENDIDIKAN KARAKTER MELALUI KEMAMPUAN MENCIPTA LAGU SEDERHANA DALAM PENDIDIKAN SENI BUDAYA BAGI SISWASEKOLAH MENENGAH PERTAMA (SMP)AbstractThe research was conducted in SMP Negeri 16 Padang, which was motivated by the music of culture and art of learning problems in curriculum-based Character Education in 2013, where some of the subject matter tends to develop the cognitive and psychomotor, more geared to the development of the affective domain. From the pattern of KI and KD field of the music of culture and art in 2013 at the junior high curriculum, competencies, knowledge and skills the art of music is not negligible, but the development of attitudes of learners through learning music is much more important. Developing Character Education through Capability Creates a Simple Song learning in the Junior Cultural Arts is one of the subject matter may be directed to the development of the educational aspects of character, to understand the attitude and response of students to the theme of simple songs that he created. There are nine steps that are applied in this study are: (1) find the idea: (2) exploration of the theme of experience and appreciation of the work: (3) stringing words according to the theme: (4) analysis of the suitability of the choice of words on the vowel sounds in rhymes and articulation: (5) selection of musical nuance and patron melody; (6) analysis of the relationship melodies and lyrics; (7) notational (number / beam) (8) makes a simple isnstrumental musical accompaniment; and (9) the presentation creation simple songs sung by music iiringan. Results showed that, with a simple song that created the students, they realize himself what he knew and understood about attitudes and behavior problems of both himself and other people. Key Words: Education Music Arts, character education, creating songs AbstrakPenelitian ini dilaksanakan di SMP Negeri 16 Padang yang dilatarbelakangi oleh masalah pembelajaran seni budaya musik dalam Kurikulum 2013 yang berbasis Pendidikan Karakter, di mana beberapa materi pelajaran yang cenderung mengembangkan ranah kognitif dan psikomotorik, lebih diarahkan kepada pengembangan ranah afektif. Dari pola KI dan KD bidang Seni Budaya Musik pada kurikulum 2013 di SMP, kompetensi pengetahuan dan keterampilan seni musik tidak diabaikn, namun pengembangan sikap peserta didik melalui pembelajaran musik jauh lebih penting. Mengembangkan Pendidikan Karakter melalui Kemampuan Mencipta Lagu Sederhana dalam pembelajaran Seni Budaya di SMP adalah salah satu materi pelajaran yang dapat diarahkan kepada pengembangan aspek pendidikan karakter, dengan memahami sikap dan tanggap siswa terhadap tema lagu sederhana yang ia ciptakan. Ada sembilan langkah yang diterapkan dalam penelitian ini yaitu: (1) menemukan ide: (2) eksplorasi tema dari pengalaman dan apresiasi karya: (3) merangkai kata sesuai tema: (4) analisis kesesuaian pilihan kata pada bunyi vokal menurut sajak dan artikulasi: (5) pemilihan nuansa musikal dan patron melodi; (6) analisis hubungan melodi dan lirik; (7) penulisan notasi (angka/balok) (8) membuat iringan musik isnstrumental sederhana; dan (9) presentasi ciptaan lagu sederhana yang dinyanyikan dengan iiringan musik. Hasil penelitian menunjukkan bahwa, dengan lagu sederhana yang diciptakan siswa, mereka menyadari sendiri apa yang ia ketahui dan pahami tentang masalah sikap dan berperilaku baik bagi dirinya maupun oranglain. Kata Kunci: Pembelajaran Seni Musik, pendidikan karakter, mencipta lagu